Netherlands Colonial Goverment Policy on Islamic Education - Ismail Ismail; Abd Mukti; Sapri Sapri (Edumaspul: Jurnal Pendidikan, 2024)
This scientific study aims to analyze in more depth the Dutch colonial government's policies towards Islamic education. This scientific study uses qualitative research methods with the type of library research. The data used in this study is secondary data, including accredited journals and books that are appropriate to the topic studied. The results of the analysis state that the Dutch colonial government's policy towards Islamic education in Indonesia was very unsupportive. The researchers based this conclusion on deviations in the application of ethical politics, the emergence of teacher ordinances, and even illegal school ordinances that are specific to educational institutions or Islamic schools. Therefore, this proves how concerned the Dutch colonial government was regarding the existence and development of Islamic education in Indonesia